2018
DOI: 10.1007/s11926-018-0776-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Current Literature on Treatments Containing Adipose-Derived Stem Cells for Osteoarthritis: a Progress Update

Abstract: Five studies in this review used cultured ADMSCs, while four studies used stromal vascular fraction and three used micro-fragmented adipose tissue to deliver ADMSCs. No studies reported serious treatment-related adverse effects and all reported improvements in clinical measures for at least one dose. This was not necessarily reflected in imaging evaluations nor were improvements always maintained. Current low-level evidence is limited due to variability in study methodology but indicates that treatments contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Generally, there are two ways of delivering AD-MSCs: i) cultured AD-MSCs, and ii) in stromal vascular fraction (SVF) [15] . SVF from adipose tissue showed a mixed cell population of polygonal and fibroblastic cells, some containing a small proportion of MSCs and lipid droplets in their cytoplasm, whereas AD-MSCs displayed a spindle-shaped morphology and a very specific homogenous stem cells population [4,15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, there are two ways of delivering AD-MSCs: i) cultured AD-MSCs, and ii) in stromal vascular fraction (SVF) [15] . SVF from adipose tissue showed a mixed cell population of polygonal and fibroblastic cells, some containing a small proportion of MSCs and lipid droplets in their cytoplasm, whereas AD-MSCs displayed a spindle-shaped morphology and a very specific homogenous stem cells population [4,15] .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there are two ways of delivering AD-MSCs: i) cultured AD-MSCs, and ii) in stromal vascular fraction (SVF) [15] . SVF from adipose tissue showed a mixed cell population of polygonal and fibroblastic cells, some containing a small proportion of MSCs and lipid droplets in their cytoplasm, whereas AD-MSCs displayed a spindle-shaped morphology and a very specific homogenous stem cells population [4,15] . While the current literature focused more on the use of AD-MSCs in patients with knee OA and showed satisfactory clinical and functional improvement, pain relief and structural regeneration of articular cartilage [2,9,11] ; clinical studies on SVF [4,8] demonstrated its chondroprotective, immunomodulatory, anti-fibrotic and anti-inflammatory properties [6] , suggesting a safe therapeutic approach for the treatment of severe knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…used adipose-derived MSCs to treat OA and they found that the treatment group had slight discomforts and bruises after the fat extraction [ 57 ]. Ranmuthu et al also reported adverse events such as local pain and swelling at the fat collection site [ 58 ]. Studies from Draganski et al proved that even if professionally trained personnel performs bone marrow harvesting, there are risks of discomfort, postoperative pain, and infection during the harvesting process, while allogeneic sources may lead to risks such as disease transmission and graft-versus-host disease [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In May 2021, we conducted a search in seven electronic databases: MEDLINE via PubMed, Epistemonikos, PEDro, DynaMed, TripDatabase, Elsevier via Clinicalkey and Cochrane Controlled Trials Register. In addition, we manually searched references from all available reviews 15 , 20 29 on SVF to verify that none were missing from our initial search. The search included the terms ‘stromal vascular fraction’, ‘knee osteoarthritis’ or ‘osteoarthritis’, ‘cartilage’, ‘adipose-derived stem cells’ or ‘adipose-derived stromal cells’, and ‘mesenchymal stem cells’ or ‘mesenchymal stromal cells’ in the title and abstract of all trial registers and databases.…”
Section: Methodsmentioning
confidence: 99%